Implementation of Village Policy in Improving Student Akhlaq through Religious Programs - Asari; Muhlisin (Saniya Institute, 2024)
The implementation of village policies to improve student morals through religious programs is a vital topic in the effort to improve student morals and ethics. This research discusses the strategies and effects of village policies on student morals through religious programs. Qualitative methods were applied with case studies in villages that actively run diniyah programs. The findings show that village policies have been successful in raising awareness of religious values and student morality. The role of religious leaders, local communities, and local government support are key factors in the success of the program. However, challenges such as limited resources and resistance to change still exist. It is recommended to adopt strategic measures such as expanding access to resources and raising public awareness about the importance of religious education. This research emphasizes the importance of the proactive role of village governments in the moral and spiritual development of the younger generation.